Potential for exploitative competition, not intraguild predation, between invasive harlequin ladybirds and flowerbugs in urban parks - Howe, Andy G; Ravn, Hans-Peter; Bressen Pipper, Christian; Aebi, Alexandre (My University, 2015)
In aphidophagous insect communities invaded by the harlequin ladybird Harmonia axyridis Pallas (Coleoptera: Coccinellidae), intraguild predation (IGP) is widely implicated in the displacement of native predators, however, indirect trophic interactions are rarely assessed. Using molecular gut-content analysis, we investigated the relative frequencies of IGP by H. axyridis on the predatory flowerbug Anthocoris nemoralis Fabricius (Heteroptera: Anthocoridae) and prey overlap for a shared prey, the lime aphid Eucallipterus tiliae L. (Hemiptera: Aphididae), in Tilia × europaea crowns in urban parks. The frequency of IGP by H. axyridis was low: 2.7 % of larvae and 3.4 % of adults tested positive for A. nemoralis DNA. The presence of lime aphid DNA in predators was higher: 56.5 and 47.9 % of H. axyridis larvae and adults, respectively, contained E. tiliae DNA, whereas 60.8 % of adult A. nemoralis tested positive for aphid DNA. Incorporating insect densities revealed that the density of H. axyridis larvae had a strong negative effect on the likelihood of detecting aphid DNA in A. nemoralis. Prey overlap for E. tiliae was widespread in space (2–13 m height in tree crowns) and time (May–October 2011) which suggests that interspecific exploitative competition, mediated by predator life-stage, more so than IGP, is an important indirect trophic interaction between co-occurring H. axyridis and A. nemoralis. Whether exploitative competition equates to displacement of A. nemoralis populations requires further investigation. Our results emphasize the need to incorporate indirect interactions in studies of insect communities following invasion, not least because they potentially affect more species than direct interactions alone.
Keywords: Biological control; environmental risk assessment